Learning Mindset In Today's Business: Leading To Innovation And Consumer-Centrix Motives - Ign Heri Satrya Wangsa (BIP's JURNAL BISNIS PERSPEKTIF, 2009)
Innovation has become relevant keywords for business that may intend to be competitive as there will be a creation of new breakthrough which has the orientation to form consumer-centrix motives. Innovative business could label consurner-centrix touch toward its products. Old resultoriented mindset will then go through how to ideally accomplish consumer's expectation. The growing number of various customized products or tailor-made products has brought an important indication that consumer has become major issue. Innovative activities could not be continuously applied unless the business has mindset to renew its cycle. As an organism, a business should have learning mindset which could motivate itself to keep innovative. This is an introductory paper which hopefully facilitates those who want to conduct thorough srudy related to learning mindset on innovation and consumer-centrix motives.